The effects of metal oxide blended activated coke on flue gas desulphurization. Issue 60 (8th June 2016) - Yang, Lin; Huang, Tian; Jiang, Xia; Li, Jianjun; Jiang, Wenju
Abstract : The objective of this study was to investigate the possibility of using some natural minerals or industrial waste containing some metal oxides to prepare modified activated coke (M/AC) for flue gas desulphurization. Abstract : The objective of this study was to investigate the possibility of using some natural minerals or industrial waste containing some metal oxides to prepare modified activated coke (M/AC) for flue gas desulphurization. The metal oxides, i.e. Fe2 O3, Co2 O3, CuO and Ni2 O3, were used as additives to prepare M/AC by a blending method. The results show that the M/AC could effectively improve desulphurization performance, and the highest sulphur capacity was obtained at 143 mg g −1 for the Ni/AC sample with a blending ratio of 12 wt%, which was higher than that of the blank sample (97 mg g −1 ). The addition of metal oxides by the blending method could affect the textural properties of M/AC evidently and the influence was different with different metal oxides and blending ratios. On the other hand, M/AC samples have higher contents of oxygen-containing functional groups, with the highest for the Ni/AC sample, and have higher contents of π–π* transition groups, compared with blank activated coke. The metal oxides loaded on the M/AC were mainly transformed to metallic particles during the activation process, and to metal sulfate and partially metal oxides after the desulphurization process.